Indian family businesses in Durban - Jithoo, Sabita (Rhodes University, Faculty of Humanities, Department of Anthropology, 1983)
From introduction: This is a study of Indian family businesses in the central business district of Durban, a sea port on the coast of Natal, in South Africa.
Keywords: East Indians -- South Africa; East Indians -- South Africa -- Economic conditions; East Indians -- South Africa -- Social life and customs; Family-owned business enterprises -- South Africa